1981
DOI: 10.3758/bf03207292
|View full text |Cite
|
Sign up to set email alerts
|

Limulus psychophysics: Increment threshold

Abstract: Prior temporal summation work had indicated that the sensory code for certain behaviors (in both Limulus and humans) can be understood if one suggests that the central nervous system analyzes the integral of the photoreceptor potential. An independent test of this suggestion is available because (in Limulus) the physiological increment threshold function obtained from the receptor potential integral is inflected, whereas that obtained from the initial transient peak of the receptor potential is not. The behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This would cause a daily variation in visual behavior. Hypothesis 2 is therefore consistent with the data from the present experiment; however, Hypothesis 2 is still subject to the same inability of Hypothesis 1 to account completely for the increment threshold data reported in Wasserman (1981).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This would cause a daily variation in visual behavior. Hypothesis 2 is therefore consistent with the data from the present experiment; however, Hypothesis 2 is still subject to the same inability of Hypothesis 1 to account completely for the increment threshold data reported in Wasserman (1981).…”
Section: Discussionsupporting
confidence: 84%
“…For example, Wasserman and Patton (1970) found that Winter animals almost never responded to a light of a fixed intensity while Spring animals almost always responded to a light of the same intensity. In a more recent study, Wasserman (1981) found that Winter animals were 0.5 log units less sensitive than Fall animals. The only difference between the present study and these earlier studies is that the present one covered all seasons of a year whereas the prior studies permit only a comparison between two adjacent seasons.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These studies have compared intracellular recordings taken from single receptors with the behavior of intact subjects. Problems studied have included: the problem of temporal summation, or the tradeoff between stimulus duration and intensity (Kong & Wasserman, 1978a, 1978bWasserman, 1978;Wasserman & Kong, 1975); the problem of the psychophysical function, relating sensation quantity to stimulus intensity (Wasserman, Felsten, & Easland, 1978, 1979Wasserman, 1981); and the problem of perceptual masking, or the effect that one stimulus has on the perception of a second stimulus , 1979a, 1979b, 1981Wasserman, Lo, & Easland, 1976).…”
mentioning
confidence: 99%